Symmetric Blind Decryption with Perfect Secrecy. (16th August 2017) - Partala, Juha
Abstract : A blind decryption scheme enables a user to query decryptions from a decryption server without revealing information about the plain-text message. Such schemes are useful, for example, for the implementation of privacy-preserving encrypted file storages and payment systems. In terms of functionality, blind decryption is close to oblivious transfer. For noiseless channels, information-theoretically secure oblivious transfer is impossible. However, in this paper, we show that this is not the case for blind decryption. We formulate a definition of perfect secrecy of symmetric blind decryption for the following setting: at most one of the scheme participants is a passive adversary (honest-but-curious). We also devise a symmetric blind decryption scheme based on modular arithmetic on a ring Z p 2, where p is a prime, and show that it satisfies our notion of perfect secrecy.